Pengaruh Ukuran Perusahaan Dan Pertumbuhan Perusahaan Terhadap Opini Audit Going Concern PT. Unilever Tbk 2014-2018 - Johandri Iqbal (universitas teuku umar, 2020)
This research was conducted at PT. Unilever Indonesia Tbk. listed on the Indonesia Stock Exchange. The data used are the financial statements of PT. Unilever Indonesia Tbk. 2014-2018, data is taken from www.idx.co.id. The number of variables studied were three variables, namely Company Size (X1), Company Growth (X2) as the independent variable, and Going Concern Audit Opinion (Y) as the dependent variable. The analysis in this study used multiple regression and the coefficient of determination test. The research location chose PT. Unilever Indonesia Tbk, because PT. Unilever Indonesia Tbk is one of the major companies for which Indonesian financial data can be researched. This reason is what makes researchers interested in conducting research on the influence of Company Size and Company Growth on the Going Concern Audit Opinion of PT. Unilever Indonesia Tbk 2014-2018. The results of this study have a simultaneous influence on firm size (X1) and company growth (X2) on going-concern audit opinion and this effect is 56.7% and the remaining 43.3% is from other unknown variables in this study. Keywords: Company Size, Company Growth, Financial Statements, Audit Opinion